Does climate directly influence NPP globally? - Chengjin Chu; Megan Bartlett; Youshi Wang; Fangliang He; Jacob Weiner; Jérôme Chave; Lawren Sack (Global Change Biology, 2016)
The need for rigorous analyses of climate impacts has never been more crucial. Current textbooks state that climate directly influences ecosystem annual net primary productivity ( NPP ), emphasizing the urgent need to monitor the impacts of climate change. A recent paper challenged this consensus, arguing, based on an analysis of NPP for 1247 woody plant communities across global climate gradients, that temperature and precipitation have negligible direct effects on NPP and only perhaps have indirect effects by constraining total stand biomass ( M tot ) and stand age ( a ). The authors of that study concluded that the length of the growing season ( l gs ) might have a minor influence on NPP , an effect they considered not to be directly related to climate. In this article, we describe flaws that affected that study's conclusions and present novel analyses to disentangle the effects of stand variables and climate in determining NPP . We re‐analyzed the same database to partition the direct and indirect effects of climate on NPP , using three approaches: maximum‐likelihood model selection, independent‐effects analysis, and structural equation modeling. These new analyses showed that about half of the global variation in NPP could be explained by M tot combined with climate variables and supported strong and direct influences of climate independently of M tot , both for NPP and for net biomass change averaged across the known lifetime of the stands ( ABC = average biomass change). We show that l gs is an important climate variable, intrinsically correlated with, and contributing to mean annual temperature and precipitation ( T ann and P ann ), all important climatic drivers of NPP . Our analyses provide guidance for statistical and mechanistic analyses of climate drivers of ecosystem processes for predictive modeling and provide novel evidence supporting the strong, direct role of climate in determining vegetation productivity at the global scale.